THE USE OF ALTERNATIVE TYPES OF OIL RAW MATERIALS NONOIL. (E Conference Zone, 2022)
In this article, the types of side effects that are an alternative to petroleum products that can be used in vehicles, the technology of their production, raw materials, advantages and disadvantages, as well as their eco – economic efficiency are presented.